DESENVOLVIMENTO DE MELHORIAS NO PROJETO DETALHADO DO MÓDULO DE TRAÇÃO DE UMA MÁQUINA PARA AGRICULTURA FAMILIAR - Kersting, Filipe; Pereira, Jean C. B.; Borges, Pablo O.; Ferreira, Antonio E. M.; Valdiero, Antonio C. (Salão do Conhecimento, 2013)
Resumo